2016
DOI: 10.1007/s12155-016-9754-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil Greenhouse Gas Emissions and Carbon Dynamics of a No-Till, Corn-Based Cellulosic Ethanol Production System

Abstract: Crop residues like corn (Zea mays L.) stover perform important functions that promote soil health and provide ecosystem services that influence agricultural sustainability and global biogeochemical cycles. We evaluated the effect of corn stover removal from a no-till, corn-soybean (Glycine max (L.) Merr) rotation on soil greenhouse gas (GHG; CO 2 , N 2 O, CH 4 ) fluxes, crop yields, and soil organic carbon (SOC) dynamics. We conducted a 4-year study using replicated field plots managed with two levels of corn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Other rainfed studies in warmer climates have also noted lower soil N 2 O emissions when crop residue is removed (Jin et al ., ; Guzman et al ., ). In contrast, rainfed studies from colder climates have shown that stover removal can increase soil N 2 O emissions (Congreaves et al ., ; Lehman & Osborne, ), possibly due to warmer soil temperatures or changes in moisture/aeration conditions that stimulate denitrifier activity. In a meta‐analysis of 28 crop residue removal studies of mostly nonirrigated systems, Chen et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other rainfed studies in warmer climates have also noted lower soil N 2 O emissions when crop residue is removed (Jin et al ., ; Guzman et al ., ). In contrast, rainfed studies from colder climates have shown that stover removal can increase soil N 2 O emissions (Congreaves et al ., ; Lehman & Osborne, ), possibly due to warmer soil temperatures or changes in moisture/aeration conditions that stimulate denitrifier activity. In a meta‐analysis of 28 crop residue removal studies of mostly nonirrigated systems, Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although increasing crop rotation complexity generally enhances SOC storage, limited SOC changes occur when continuous corn is converted to a corn-soybean rotation (West & Post, 2002). Thus, similar to SOC losses observed under continuous corn, residue removal in a rainfed corn-soybean system also resulted in SOC losses (Lehman & Osborne, 2016). Other corn rotational systems (e.g., corn-wheat Triticum aestivum L.) have shown numerical but not statistically significant SOC losses after crop residue removal (Lemke et al, 2010;Huang et al, 2013).…”
Section: Soil Organic Carbon Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of an effect in the present study challenges the assumption that crop residue removal will reduce N 2 O emissions based on IPCC methodology (IPCC, ). A wide variety of responses to residue removal have been observed and the fact that field results do not always support top‐down GHG accounting protocols has been argued in previous studies (Congreves et al, ; Hao et al, ; Lehman & Osborne, ; Yao et al, ). Together these findings suggest the impacts of residue removal cannot easily be predicted for maize production in this region, which presents a challenge for accurately estimating the net GHG impacts of cellulosic biofuel production.…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with IPCC emission factors, a number of previous studies have found that residue removal decreases N 2 O emissions (Abalos, Sanz‐Cobena, Garcia‐Torres, Groenigen, & Vallejo, ; Jin et al, ; Mutegi, Munkholm, Petersen, Hansen, & Petersen, ; Yao et al, ). However, studies have also shown N 2 O emissions can either increase or remain unchanged with crop residue removal (Congreves, Brown, Németh, Dunfield, & Wagner‐Riddle, ; Hao, Chang, Carefoot, Janzen, & Ellert, ; Lehman & Osborne, ; Yao et al, ). Increased N 2 O emissions may be due to larger soil temperature fluctuations or changes in moisture/aeration conditions compared to the practice of incorporating crop residues.…”
Section: Introductionmentioning
confidence: 99%